Próba określenia wpływu terapii BEMER na wybrane wskaźniki krwi w ramach procesu odnowy biologicznej po wysiłku wytrzymałościowym. Studium przypadku - Posłuszny, Mariusz (Journal of Education, Health and Sport, 2015)
Posłuszny Mariusz. Próba określenia wpływu terapii BEMER na wybrane wskaźniki krwi w ramach procesu odnowy biologicznej po wysiłku wytrzymałościowym. Studium przypadku = An attempt to determine the effect of BEMER therapy on selected blood indicators in the process of biological restitution after endurance effort. A case study. Journal of Education, Health and Sport. 2015;5(10):121-140. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32524 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A121-140 https://pbn.nauka.gov.pl/works/660483 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. Próba określenia wpływu terapii BEMER na wybrane wskaźniki krwi w ramach procesu odnowy biologicznej po wysiłku wytrzymałościowym. Studium przypadku An attempt to determine the effect of BEMER therapy on selected blood indicators in the process of biological restitution after endurance effort. A case study Mariusz Posłuszny Uniwersytet Przyrodniczy, Poznań Streszczenie Wstęp. Mikrokrążenie należy postrzegać jako rodzaj żywego organu będącego składową układu sercowo-naczyniowego odpowiedzialnego za prawidłową dystrybucję między innymi tlenu do komórek. Według producenta terapia systemem BEMR przy zastosowaniu kompleksowym lub uzupełniającym doskonali podstawowe procesy fizjologiczne, angiokinezę mikrokrążenia, doprowadzenie składników odżywczych i tlenu do komórek mięśniowych. Dzięki określonej modulacji biorytmicznej uzyskuje się synergiczny wpływ również na pierwotne i wtórne krążenie oraz nieco większe naczynia krwionośne. Celem badań jest ocena wpływ sygnału BEMER na wybrane wskaźniki krwi w ramach procesu odnowy biologicznej po wysiłku wytrzymałościowym. Opis przypadku. Materiał i metody. Badany mężczyzna realizujący zdrowy styl życia poddał się oznaczeniu wybranych wskaźników krwi w dwóch edycjach pomiarów po wysiłku wytrzymałościowym w czasie restytucji samoistnej i odnowie wspomaganej terapią BEMER: NEU%, LYM%, BASO %, EOS%, MONO%, tHb, BE, BEACT, BB, HHb, cHCO3, PO2, SO2 (c), O2Hb, MeHb, COHb. Uzyskane wyniki. Pozytywne wyniki zaobserwowano w większości mierzonych cech krwi. Przy czym różnie prezentowała się ich konfiguracja w trakcie 5 dniowego cyklu pomiarowego. Najbardziej pozytywne zmiany zaobserwowano w EOS%, HHb, cHCO3, PO2, SO2(c), O2Hb, COHb, BE, BEakt, mniej znaczące w NEU%, LYM%, BASO%, MONO%, tHb, cHCO3, BB, MeHb. Wnioski. (1) Zastosowana metodyka i profil sygnału BEMER poprzez zwiększenie światła naczyń mikrokrążenia wpływa zróżnicowanie na wielkość wybranych wskaźników krwi, (2) Zastosowanie stymulacji BEMER w odnowie biologicznej po wysiłkach wytrzymałościowych u mężczyzn w 5-6 dekadzie życia może być uzasadnione, (3) Uzyskane jednostkowe wyniki z przeprowadzonych pomiarów, nie mogą być podstawą do uogólnionych wniosków nad wpływem sygnału BEMER na restytucję po wysiłku wytrzymałościowym. Mogą być jedynie próbą wskazania kierunku dalszych dociekań nad modyfikacją metodyki stosowania wielowymiarowego strukturalnie sygnału BEMER i intensyfikacją odnowy biologicznej po różnych wysiłkach. Słowa kluczowe: terapia BEMER, wskaźniki krwi, restytucja fizjologiczna, odnowa biologiczna. Summary Introduction. Microcirculation should be perceived as a living organ that is part of cardio-vascular system responsible inter alia for proper distribution of oxygen to cells. According to the manufacturer, BEMER therapy, applied both as comprehensive or complementary treatment, improves basic physiological processes, microcirculatory angiokinesis and oxygenation and nutrition of muscle cells. Also, due to its particular biorhythmic modulation, it exerts a synergic influence on primary and secondary circulation as well as on slightly bigger blood vessels. The aim of the study is to assess the effect of BEMER signal on selected blood indicators in the process of biological restitution after endurance effort. A case study. Material and methods. The studied male individual lives a healthy life-style and he subjected himself to the markings of selected blood indicators after endurance effort in two consecutive rounds of measurements – during spontaneous restitution and during restitution enhanced with BEMER therapy: NEU%, LYM%, BASO %, EOS%, MONO%, tHb, BE, BEACT, BB, HHb, cHCO3, PO2, SO2 (c), O2Hb, MeHb, COHb. Results. Positive results were observed in most of the measured blood features. However, their configuration during 5-day measurement cycle varied. The most positive changes occurred in the following: EOS%, HHb, cHCO3, PO2, SO2(c), O2Hb, COHb, BE, BEakt, less significant for NEU%, LYM%, BASO%, MONO%, tHb, cHCO3, BB, MeHb. Results. (1) Applied methodology and BEMER signal profile, through increasing the lumen of microcirculation vessels, variously affects the values of selected blood indicators. (2) The use of BEMER stimulation in the process of biological restitution in males in their fifties / sixties may be justified. (3) The individual results achieved in the course of the study, however, may not serve as a basis for drawing general conclusions on the effect of BEMER signal on the process of biological restitution after endurance effort. Instead, they may be treated as an attempt at showing the direction for further research on the possible changes in the application method of the structurally multidimensional BEMER signal as well as on the intensification of biological restitution after various physical efforts. Key words: BEMER therapy, blood indicators, physiological restitution, biological restitution.